Progress of Construction Project Information System Based on SMS Gateway - Hendri Ahmadian; Dedi Satria; Safrijal Kurniawan (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2018)
Management of reporting project progress and material inventory reporting otherwise known as supply chain management is needed, namely to ensure that the project has progress or not. Based on the reporting activities that have been carried out there are activities that are less effective than the system of recording progress reporting and the supply of construction materials in the field, namely reporting time and recording system. So because this paper aims to explain the making of information systems the progress of construction projects that are integrated with the reporting system of inventory of empty materials using the SMS gateway. The methodology is built using the phases of context diagrams, data flow diagrams and entity relationships. The system is built using PHP programming, mySQL database and Gammu. The results of the study show that the project progress information system has produced project reports and progress in the form of web pages. As well as a brief report on the progress of the project, Hanphone has received an SMS. Research is expected to benefit construction companies so that reporting can be more effective and efficient.